(untitled) (KONFERENSIYA, 2025)
The global dissemination of scientific knowledge depends heavily on the work of translators, who facilitate communication across linguistic and cultural boundaries. This article explores the multifaceted role of translators in supporting international research, highlighting their contributions to bridging language gaps, preserving conceptual accuracy, and enabling collaborative scientific efforts. Translators ensure that complex terminology and methodological details are conveyed precisely, reducing the risk of misinterpretation and enhancing the reliability of research findings. Moreover, by assisting in multinational projects, conferences, and publications, they foster inclusive knowledge exchange and promote the integration of diverse perspectives within the global scientific community. Recognizing the critical role of translators underscores their importance in advancing research accessibility, collaboration, and innovation worldwide